Management of post-hysterectomy urinary incontinence with composite Ayurveda treatment – A case report - Ranjani Karthik Pandit (Journal of Ayurveda and Integrative Medicine)
This is a case report of a patient who developed urinary incontinence after undergoing abdominal hysterectomy. This was successfully treated with Ayurvedic treatment procedures. A 63-year-old lady was suffering from urinary incontinence, which developed after hysterectomy. It did not subside even after undergoing trans vaginal taping. She was treated with Ayurvedic procedures and medicines for a period of 2 and a half months from 4th of March 2016 to 26th of May 2016. Matrabasti (medicated enema) and Madhutailika basti (enema treatment with honey and oil), along with other palliative medicines – Sukumara ghrita, Chandraprabha vati, Shilajatu, Mahakalyanaka kashaya, Mamsapachaka ghana vati and Mahatiktaka ghrita were given to the patient. Urinary incontinence reduced to dribbling of urine after Matra basti and after the second course of Basti (medicated enema), that is after one and half months, patient stopped using diapers and was relieved from incontinence. This case report summarises the effective management of urinary incontinence by adopting basti (enema) treatment along with other palliative ayurvedic medicine.